PRINTO/PRES international website for families of children with rheumatic diseases: www.pediatric-rheumatology.printo.it. Issue 7 (10th March 2005) - Ruperto, N; Garcia-Munitis, P; Villa, L; Pesce, M; Aggarwal, A; Fasth, A; Avcin, T; Bae, S-C; Balogh, Z; Li, C; De Inocencio, J; Dibra, M; et al.
Abstract : Objective: To prepare a website for families and health professionals containing up to date information about paediatric rheumatic diseases (PRD). Methods: Firstly, paediatric rheumatology centres and family self help associations were surveyed to characterise current clinical practice of physicians providing care for children with PRD, research activities, and training facilities of each centre. Secondly, international consensus was reached on the content of the website. Finally, the website was developed and the texts translated. Results: The web page contains three main sections: ( a ) description for families of the characteristics of 15 PRD; ( b ) list of paediatric rheumatology centres; ( c ) contact information for family self help associations. A version for 45 countries in 52 languages (with another three in progress) is now available on the web. 291 surveys from 171 centres and 102 family associations were received from 42 countries. The median proportion of time spent in paediatric practice in the centres examined was 100%, with 70% of this time dedicated to paediatric rheumatology. 90% of the centres were willing to perform clinical trials in the future. Conclusions: The PRINTO/PRES website provides a well defined and competent set of information about PRD, with appropriate multiple translated versions and easy web navigational direction.